PROTESTANT CHORALE AND METHODS OF ITS PROCESSING - Petresku Ya. V. (International Journal of Innovative Technologies in Social Science, 2021)
The article is devoted to the consideration of the Protestant chorale, the preconditions of its origin and the first examples. The situation from the history of the early Lutheran church is described, when Martin Luther introduced communal choral singing. The main task set in the work is to analyze the main methods of processing Protestant chorales in the works of prominent Western European and domestic composers. Several vocal, instrumental and vocal-instrumental genres are considered, which are based on choral. It is noted that the most common means of processing the chorale is its harmonization, designed for both choral and organ performance. In the Renaissance and Baroque, the practice of creating figures on the choral became quite common, as well as the use of the choral as the theme of the fugue – fugue choral. Another way of elaborating the chorale was the technique of cantus firmus, while the theme of the chorale was located in the lower voice or in the tenor in rhythmic expanse, forming the basis of the whole composition. One of the leading genres of organ music – choral preludes – is considered, special attention is paid to the works of JS Bach. The principle of construction of choral fantasies is analyzed separately. Among other genres, parties, toccatas, masses, oratorios, and other works were created on the basis of chorales. In conclusion, there is a modern tendency to return to the practice of using chant in the liturgy in its original form, as they sounded earlier.